Becoming "Copwise": Policing, Culture, and the Collateral Consequences of Street‐Level Criminalization. Issue 2 (June 2016) - Stuart, Forrest
Abstract : Over the last four decades, the United States has witnessed a historic expansion of its criminal justice system. This article examines how street‐level criminalization transforms the cultural contexts of poor urban communities. Drawing on five years of fieldwork in Los Angeles' Skid Row–the site of one of the most aggressive zero‐tolerance policing campaigns to date–the study finds that residents develop and deploy a particular cultural frame–"cop wisdom"–by which they render seemingly‐random police activity more legible, predictable, and manipulable. Armed with this interpretive schema, "copwise" residents engage in new forms of self‐presentation in public, movement through the daily round, and informal social control in order to deflect police scrutiny and forestall street stops. While these techniques allow residents to reduce unwanted police contact, this often comes at the expense of individual and collective well‐being by precluding social interaction, exacerbating stigma, and contributing to animosity in public space.